A Comparative Analysis of Integrated Boost Flyback Converter using PID and Fuzzy Controller - R.Samuel Rajesh Babu (Institute of Advanced Engineering and Science, 2015)
This paper presents a comparative analysis of Integrated boost flyback converter for Renewable energy System. IBFC is the combination of boost converter and fly back converter. The proposed converter is simulated in open and closed loop using PID and FUZZY controller. The Fuzzy Logic Controller (FLC) is used reduce the rise time, settling time to almost negligible and try to remove the delay time and inverted response. The performance of IBFC with fuzzy logic controller is found better instead of PID controller. The simulation results are verified experimentally and the output of converter is free from ripples and has regulated output voltage.